1990
DOI: 10.1073/pnas.87.13.5031
|View full text |Cite
|
Sign up to set email alerts
|

T-cell antigen CD28 mediates adhesion with B cells by interacting with activation antigen B7/BB-1.

Abstract: Studies using monoclonal antibodies (mAbs) have implicated the homodimeric glycoprotein CD28 as an important regulator of human T-cell activation, in part by posttranscriptional control of cytokine mRNA levels. Although the CD28 antigen has functional and structural characteristics of a receptor, a natural ligand for this molecule has not been identified. Here we show that the CD28 antigen, expressed in Chinese hamster ovary (CHO) cells, mediated specific intercellular adhesion with human lymphoblastoid and le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
330
2
3

Year Published

1996
1996
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 647 publications
(342 citation statements)
references
References 38 publications
7
330
2
3
Order By: Relevance
“…Besides signalling through the T cell receptor/CD3 complex costimulatory molecules play an essential role. Both in vivo and in vitro it has been demonstrated that interaction of CD28 on T cells with its ligand B7 on APC fulfils this role [14]. In the present study, performed in cultures on Ficoll-Hypaque-isolated PBMC, in HIV-1 asymptomatic and in HIV ÿ individuals, T cell responses to CD3 plus CD28 MoAb were considerably enhanced ( 10-fold) compared with T cell responses to CD3 MoAb alone.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Besides signalling through the T cell receptor/CD3 complex costimulatory molecules play an essential role. Both in vivo and in vitro it has been demonstrated that interaction of CD28 on T cells with its ligand B7 on APC fulfils this role [14]. In the present study, performed in cultures on Ficoll-Hypaque-isolated PBMC, in HIV-1 asymptomatic and in HIV ÿ individuals, T cell responses to CD3 plus CD28 MoAb were considerably enhanced ( 10-fold) compared with T cell responses to CD3 MoAb alone.…”
Section: Discussionmentioning
confidence: 46%
“…The interaction of the membrane antigen CD28, present on T cells with the counterstructure B7, on antigen-presenting cells (APC) supplies a costimulatory activation signal for T cell proliferation [14]. CD28 is expressed on almost all normal CD4 T cells and on most circulating CD8 T cells [15].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, we have found that CD28 was expressed with its ligand CD86 (but not CD80) on myeloma cells, 13 and it has been documented that CD28 mediated adhesion of T cells with B cells by interacting with its ligand. 23 Of note, although we and others were unable to define a function of CD28 on myeloma cells, this molecule is clearly functional. 13,24 Finally, the mechanisms involved in the upregulation of CD28, as those involved in that of CD56, remain unknown.…”
Section: Discussionmentioning
confidence: 67%
“…8 CD80 and CD86 bind to CD28 on T cells, induce serine/threonine phosphorylation of CD28, 9 and transduce signals important for T cell clonal expansion. [10][11][12][13] The CD80/86-CD28 interaction is a necessary and sufficient costimulant for CD8 + CTL generation in the absence of exogenous help, 14 and interaction between antigen-MHC complex and the TCR without costimulation may lead to T cell clonal anergy or apoptosis. 15 Inoculation of tumor cells transduced with CD80 enhances the induction of antitumor immunity.…”
Section: Introductionmentioning
confidence: 99%